An Alkali-Halostable Endoglucanase Produced Constitutively by a Bacterium Isolated from Sambhar Lake in India with Biotechnological Potential - Sar, Abhijit; Pal, Srikanta; Islam, Samima; Mukherjee, Puja; Dam, Bomba (Proceedings of the National Academy of Sciences, India. Section B: Biological sciences, 2021)
Endoglucanase, particularly those, which can withstand extreme conditions are in demand in different industrial settings. In this direction, a halophilic cellulolytic bacterial strain EN1 was isolated from decomposed wood particles of India’s largest inland hypersaline Sambhar Lake in Rajasthan. Based on 16S rRNA gene sequence homology, the bacterium was identified as Salisediminibacterium halotolerans . It constitutively secretes extracellular endoglucanase in heterotrophic culture supernatant supplemented with or without carboxy-methyl cellulose. EN1 endoglucanase is active at pH 8.0–11.0, and 10–30% NaCl with optimum values of pH 11.0, and 25% NaCl. Under these optimum conditions, the enzyme retained up to 90% activity for 8 h. Activity was enhanced by some metal ions (5 mM) in order of Cu 2+ (273%), Ni 2+ (139%) and Fe 2+ (125%); and decreased by Mg 2+ (72%) and EDTA (56%). The enzyme was stable in different organic solvents (30% v/v), namely ethanol (108%), hexane (95%), methanol (93%), and iso-propanol (92%). The endoglucanase was effectively used for in situ saccharification of alkali-pretreated rice straw with 50 µg mL −1 reducing ends released after 120 h. These unique features of the extracellular endoglucanase reported for the first time from the genera Salisediminibacterium indicate its prospects in different industrial settings particularly for bioethanol production.